SAT0065 Effectiveness and Drug Adherence of Biologic Monotherapy in Danish Rheumatoid Arthritis Patients: A Cohort Study of Clinical Practice in the Danbio Registry. (10th June 2014) - Jørgensen, T.; Kristensen, L.; Christensen, R.; Bliddal, H.; Lorenzen, T.; Hansen, M.; Østergaard, M.; Jensen, J.; Zanjani, L.; Laursen, T.; Butt, S.; Dam, M.; et al.
Abstract : Background: Concurrent use of methotrexate (MTX) and a biologic is generally the standard-of-care in patients with RA who have disease activity despite MTX. It has been estimated that between 10 and 30% of RA patients are MTX-intolerant (1). For patients who are prescribed treatment with a biologic agent and not tolerating MTX, biological monotherapy may be considered. From DANBIO it has been estimated that 19% of RA patients in Denmark are in biologic monotherapy (2). Objectives: To elucidate the effectiveness (CDAI remission rates) and drug adherence of bDMARD therapies prescribed as monotherapy in Danish RA patients. Methods: All RA patients, treated with bDMARDs registered in DANBIO as initiating bDMARD as monotherapy, i.e. without concomitant conventional synthetic DMARDs (csDMARDs), from May 1 2011 to April 30 2013, were eligible for inclusion (2). Descriptive statistics for effectiveness and drug adherence of bDMARD monotherapy were calculated. Results: 775 patients were included (77% women, disease duration (mean [SD]): 12.6 [10.8], age: 56.0 years [12.9], 71% IgM-RF positive, CDAI: 21.1 [14.5], and DAS28: 4.4 [1.6]. At 6 months follow-up CDAI remission rates were principally separated into two clusters; a group with "poor" (0-10%) remission rates (consisting of abatacept [0/11], certolizumab [1/10] and infliximab [2/32]), and a group with "good" (above 20%) remission rates (adalimumab [35/124], etanercept [46/215], golimumab [4/16] and tocilizumab [23/86]), with rituximab in between [15%; 10/69]) (Figure). Overall, DAS28 remission was achieved in 41% (242/587), with similar pattern of remission between drugs as CDAI remission rates. With the exception of patients treated with infliximab (14%) and rituximab (16%), around one third of the patients achieved an ACR50 response (105/339). After 2 years of monotherapy, the proportion of patients still on drug was more than two thirds, when excluding infliximab. As illustrated in the figure the drug adherence rate was apparently highest for etanercept and adalimumab, and in a post hoc analysis, infliximab had significantly poorer drug adherence when compared to all the other bDMARDs (p<0.01). Conclusions: At 6 months' follow-up a "poor" remission rate group (abatacept, certolizumab and infliximab), and a "good" remission rate group (adalimumab, etanercept, golimumab and tocilizumab), with rituximab in between, were found in patients with RA treated with biologics in monotherapy in routine care. References: Yazici Y, Shi N, John A. Utilization of biologic agents in rheumatoid arthritis in the United States: analysis of prescribing patterns in 16, 752 newly diagnosed patients and patients new to biologic therapy. Bull NYU Hosp Jt Dis 2008;66(2):77-85. Jørgensen T.S. et al.The Prevalence of Biological Monotherapy among Rheumatoid Arthritis Patients (RA) in Denmark: Results from the Danish Nationwide DANBIO Registry. ACR congress 2013, poster no. 1478 Acknowledgements: This study was supported by the Oak Foundation and Roche Denmark. Disclosure of Interest: T. Jørgensen: None declared, L. Kristensen Consultant for: AbbVie, BMS, MSD and Pfizer, R. Christensen: None declared, H. Bliddal Grant/research support: Abbvie, Roche, Pfizer, and NOVO, Consultant for: Roche, Pfizer and BMS, T. Lorenzen Consultant for: Advisory Board member Roche and Pfizer, M. Hansen Consultant for: AbbVie and Roche, M. Østergaard Grant/research support: Abbott, Bristol- Myers Squibb, Centocor, GlaxoSmithKline, Janssen, Merck, Mundipharma, Novo Nordisk, Pfizer, Schering-Plough, Roche UCB, and Wyeth, Consultant for: Abbott, Bristol- Myers Squibb, Centocor, GlaxoSmithKline, Janssen, Merck, Mundipharma, Novo Nordisk, Pfizer, Schering-Plough, Roche UCB, and Wyeth, J. Jensen: None declared, L. Zanjani: None declared, T. Laursen: None declared, S. Butt: None declared, M. Dam: None declared, H. Lindegaard Consultant for: Lilly, MSD, Nordpharma and Roche, J. Espesen: None declared, O. Hendricks: None declared, P. Kumar: None declared, A. Kincses: None declared, L. Larsen: None declared, M. Andersen: None declared, E. Næser: None declared, D. Jensen: None declared, J. Grydehøj: None declared, B. Unger: None declared, N. Dufour: None declared, V. Sørensen: None declared, S. Vildhøj: None declared, I. Hansen Consultant for: Roche, Pfizer og MSD, J. Raun: None declared, N. Krogh: None declared, M. Hetland Grant/research support: Pfizer, ROche og MSD DOI: 10.1136/annrheumdis-2014-eular.3651